Factors affecting the continuation of contractor participation in the tender process for the construction services project at the center for policy research and development and application of technology – research and development agency ministry of pub - Arteti, Novi; ., Syafwandi; Susetyo, Budi (International Journal of Engineering and Technology, 2020)
The application of new technology as a result of research and development carried out by the Research and Development Agency of the Ministry of Public Works and Public Housing is one of the efforts for technological needs in infrastructure development. The implementation of technology implementation activities still faces many obstacles, one of which is the tender process. Project Characteristics Factors, Capability of Contractors and Application of New Technology can influence whether the contractor will continue or stop the tender process. This research is based on a sample of respondents from related parties including goods / service providers (contractors), work owners and groups of goods / services procurement units. The results of the data obtained were analyzed with the partial least-squares structural equation model (PLS-SEM). The analysis shows that the ability of the Contractor has the greatest influence on the Tender Process. This means that the contractor's resources are the main force to carry out the project so that it is not too dependent on other parties. Thus, it can be concluded that the consideration of ownership of the contractor's resources becomes a factor for the contractor to continue the tender process that he follows by making an offer. Because with its capital and equipment, the contractor will be able to offer more efficiently.Â